The Analysis of Metaphor Translation in the Novel Angels and Demons by Dan Brown - Riski Nur Ilahi; Sufil Lailiyah; Ahmad Yusuf Firdaus (Faculty of Letters, Universitas Abdurachman Saleh Situbondo, 2019)
This research analyzed metaphor translation in the novel of Angels and Demons with the purposes to analyzing the technique of translation and to know the quality of metaphor translation found in the novel Angels and Demons. The data were analyzed by using the theory of metaphor by Larson (1998), technique of translation used theory of Molina and Albir (2002) and quality of translation used Translation Quality Assessment theory by Nababan (2012). The analysis started by analyzing metaphorical expression, classifying the technique of translation and identifying the quality of translation based on the theory that was use for this research. The findings revealed that there were 119 metaphor expressions with 84 live metaphors and 35 dead metaphors. The metaphor translation used nine techniques of translation and the quality of metaphor translation was qualified by the assessment 2.90.